Unraveling complexation and enantioseparation of a new chiral‐at‐uranium complex to chiral pesticides R/S‐malaoxons - Guo, Meng‐zhen; Ouyang, Wen‐jun; Wang, Yun; Kong, Xiang‐he; Xiao, Xi‐lin; Nie, Chang‐ming; Peng, Guo‐wen (Applied organometallic chemistry, 2024)
Unraveling uranium complexes has become a popular study topic in recent years to address the problem of spent fuel treatment. An important and promising investigation is the enantiomer separation of chiral organophosphorus pesticides (OPs) via uranyl‐containing receptors. Among them, malaoxon (MLX), as a chiral OP with high toxicity and good selectivity, is controversial because of the different toxicity differences caused by the R and S configurations to target and non‐target organisms. Therefore, it is crucial to explore effective methods for separating its enantiomers. In this work, a novel 2‐(9‐[1H‐pyrazole‐1‐carbonyl]‐1,10‐phenanthrolin‐2‐yl)‐1H‐inden‐1‐one (HPIDO) ligand, which combines with uranyl to form the chiral‐at‐uranium complex (Uranyl‐HPIDO receptor), was designed for the enantioseparation of R/S‐malaoxons (R/S‐MLXs). Based on density functional theory (DFT), we explored the potential coordination modes between the Uranyl‐HPIDO receptor and R/S‐MLXs at various sites. The analyses of bonding properties, orbital interactions, and weak interactions of intramolecular groups of the complexes, along with the study of thermodynamic properties, revealed that the Uranyl‐HPIDO receptor preferred to bind to the phosphoryl oxygen (O5) of R/S‐MLXs to form stable complexes. Good enantioseparations of the two enantiomers were achieved in various solvents (water, n‐Butanol, n‐Octanol, dichloromethane, propanoic acid, toluene, and cyclohexane); the separation factors (SFR/S) ranged 21–853, and the enantioselectivity coefficients (ESCR/S) were more than 95%. The findings could theoretically offer useful information and guidance for the separation of R/S‐MLXs, in addition to providing fresh concepts for the creation of novel uranyl receptors. A novel chiral‐at‐uranium complex (Uranyl‐HPIDO) was designed for enantioseparation of R/S‐malaoxons (R/S‐MLXs). Based on density functional theory, we unraveled complexation between Uranyl‐HPIDO and R/S‐MLXs. The results indicated that Uranyl‐HPIDO preferred to bind to phosphoryl oxygen of R/S‐MLXs to form stable complexes and realized the enantioseparation of chiral MLXs.